Pornography addiction : A case study - Nurhikmah, Mubarak Ali; Muhammad Baqir, Abdullah; Samsiah, Jayos; Farah Hanani, Kamaruddin (Human Resource Management Academic Research Society, 2022)
This article is about a case study of a pornography addict who is still in the process of selfrehabilitation. Pornography is a bad and unacceptable act because it is not only prohibited in terms of moral ethics but also in religion aspects. Pornography is also one of the trafficked forms of sexual exploitation. Other than that, law enforcement and internet filtering software seem to be not an absolute solution to the pornography issue. A module or intervention is needed to be built to guide a pornography addict rehabilitating independently on their own with the help of professionals. The methodology and the research design in this study is a case study and qualitative respectively in which the interviewee is an ex client of researcher’s previous counselling session. This study forms several themes which are the causes, effects and interventions of pornography addiction. The analysis of the study also found that there are still effects of pornography addiction that disrupt the respondent’s thoughts in her daily life. These factors can assist counselors in formulating effective Islamic approach to tackle the issue, whether at the level of protection, prevention or rehabilitation. The future researchers are ought to focus more on finding an intervention that relates to the conventional counselling and the perspectives of Islam which is called Islamic Cognitive Behavioral Theory.